Genetic Polymorphism of Manganese Superoxide Dismutase in Behçet’s Disease - Efkan UZ; H. Ramazan YILMAZ; Ramazan YAĞCI; İsmail AKYOL and Tuğba ERSOY and Gülten SUNGUR and Ayşe YİĞİT and Sunay DUMAN and Ömer AKYOL (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the genetic association between single nucleotide mutation in mitochondrial manganese superoxide dismutase and a Behçet’s disease (BD) population by using molecular techniques. Patients and methods: Ninety-three BD patients (45 males, 48 females; mean age 33.15±8.99 years; range 17 to 65 years) and 125 controls (58 males, 67 females; mean age 28.33±7.31 years; range 18 to 62 years) were genotyped by polymerase chain reaction-restriction fragment length polymorphism method. The genotypic distributions in BD patients and controls were consistent with the Hardy-Weinberg equilibrium. Results: Significant differences were observed between BD patients and controls in terms of genotypic distribution. Frequencies of alanine (Ala)/Ala, Ala/valine (Val), and Val/Val were 14.0% (n=13), 45.2% (n=42), and 40.9% (n=38) in BD patients and 21.6% (n=27), 53.6% (n=67), and 24.8% (n=31) in controls, respectively (p=0.033). Conclusion: The Val/Val genotype of the manganese superoxide dismutase gene is associated with the physiopathology of BD in a group of Turkish patients.